2017
DOI: 10.1073/pnas.1619508114
|View full text |Cite
|
Sign up to set email alerts
|

Determining the factors driving selective effects of new nonsynonymous mutations

Abstract: The distribution of fitness effects (DFE) of new mutations plays a fundamental role in evolutionary genetics. However, the extent to which the DFE differs across species has yet to be systematically investigated. Furthermore, the biological mechanisms determining the DFE in natural populations remain unclear. Here, we show that theoretical models emphasizing different biological factors at determining the DFE, such as protein stability, back-mutations, species complexity, and mutational robustness make distinc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
159
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(168 citation statements)
references
References 54 publications
9
159
0
Order By: Relevance
“…Groups of species evolving under small long-term N a are further away from their optimum, compared to larger-N e groups, due to an increased rate of fixation of deleterious mutations at equilibrium, so they are predicted to undergo a larger proportion of beneficial, compensatory mutations. Empirical analyses of SFS based on large samples in humans and flies are consistent with the hypothesis that humans are on average more distant to their optimum than flies (11).…”
Section: What Are the Determinants Of ω A Across Distantly Related Taxa?supporting
confidence: 61%
See 3 more Smart Citations
“…Groups of species evolving under small long-term N a are further away from their optimum, compared to larger-N e groups, due to an increased rate of fixation of deleterious mutations at equilibrium, so they are predicted to undergo a larger proportion of beneficial, compensatory mutations. Empirical analyses of SFS based on large samples in humans and flies are consistent with the hypothesis that humans are on average more distant to their optimum than flies (11).…”
Section: What Are the Determinants Of ω A Across Distantly Related Taxa?supporting
confidence: 61%
“…In particular, one key assumption of the MK approach is that the long-term N e , which determines ω, is equal to the short-term N e and can therefore be estimated from polymorphism data.This appears unlikely to be generally true, and ancient fluctuations in N e could in principle fault the MK rationale (12,23,24). Eyre-Walker (24) theoretically considered the problem of a single ancient change in N e and showed that an expansion in population size, even if old, could lead to overestimation of the adaptive substitution rate, a bias that could create spurious positive correlation between ω a and N e and that we need to keep in mind when interpreting this type of estimates.The first applications of the MK method to large-scale data sets indicated that the adaptive rate is higher in Drosophila than in humans (11,13,14), consistent with the prediction of more efficient adaptation in large populations and with the hypothesis that mutation limits adaptation. These studies, however, were focusing on the α=ω a /(ω a +ω na ) statistics, i.e., the proportion of amino-acid substitutions that result from adaptation.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Nearly all deleterious mutations in nonhuman mammals are found in the coding part of the genome and are typically missense mutations, that is, those which cause amino acid changes in the corresponding protein. However, many missense mutations do not cause a disease (Huber, Kim, Marsden, & Lohmueller, 2017;. Here, we classify mutations into one of two classes: "deleterious" or "neutral."…”
Section: Introductionmentioning
confidence: 99%